Literasi Baca dan Tulis Pada Mata Pelajaran Pendidikan Agama Islam Kelas X di SMAN 02 Kecamatan Kapur IX Kabupaten Lima Puluh Kota - Isyah Radhiyah; Januar Januar; Iswantir Iswantir; Afrinaldi Afrinaldi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This thesis describes several problems, namely 1) the problematic application of literacy in Islamic religious education subjects at SMAN 02, Kapur IX District. 2) supporting factors and inhibiting factors in implementing literacy in Islamic religious education subjects at SMAN 02 Kapur IX District. The method used in research studies in this thesis is descriptive with a qualitative approach. The data collection techniques used in this research are: observation, interviews, documentation. The results of the research concluded that the problems with the literacy program in Islamic Religious Education that occurred at SMAN 02, Kapur IX District for the 2023/2024 class It was shown in interviews that there was a lack of motivation given by teachers to students when implementing literacy. Teachers also do not focus too much on implementing literacy because teachers consider literacy as additional learning and students' interest in literacy is still low. The contributing factor to the problem of implementing literacy in Islamic religious education subjects at SMAN 02, Kapur IX sub-district is that the school principal has informed the students' parents that they will be facilitated to support literacy activities, giving teachers encouragement to supervise literacy activities. The inhibiting factors are the lack of non-textbooks in schools and students' feelings of laziness.